The Influence of Workforce Diversity on Organizational Performance in the UAE Hospitality Sector: The Moderating Role of HR Practices - Osama Khassawneh; Tamara Mohammad (SAGE Open)
The aim of this paper is to investigate the impact of workforce diversity on organizational performance (OP) from the perspective of resource-based view (RBV) theory in the context of the hospitality sector in the United Arab Emirates (UAE). We suggest training and performance appraisal as moderators. Sequential regression analysis was applied, including information from directors, unit managers, supervisors, low-level workers, and customers, as well as financial outcomes from 167 organizations in the UAE (683 full-time employees) in the hospitality sector, including hotels, restaurants, theme parks, travel agents, recreational centers, and museums. This analysis assisted in supporting the hypotheses. The findings confirm that there is a positive relationship between diversity and OP. Additionally, the emphasis on training and performance appraisal will strengthen this relationship and lead to higher organizational performance. This improvement is expected to increase customer satisfaction and sales growth. Researchers have emphasized the necessity of conducting a comprehensive investigation to fully understand the impact of diversity on OP. In this regard, we propose that training and performance appraisal serve as potential tools to enhance OP through diversity.